Second generation bioethanol production at high gravity of pilot-scale pretreated wheat straw employing newly isolated thermotolerant yeast Kluyveromyces marxianus DBTIOC-351. Issue 47 (27th May 2015) - Saini, Jitendra Kumar; Agrawal, Ruchi; Satlewal, Alok; Saini, Reetu; Gupta, Ravi; Mathur, Anshu; Tuli, Deepak
<x xml:space="preserve">Abstract</x> Application of thermotolerant yeast Kluyveromyces marxianus DBTIOC-35 in SSF decreases overall process time, and increases productivity and yield by allowing elimination of presaccharification step and use of high biomass concentration, respectively.